Efficacy of Prenatal Yoga on Second Stage Progress in Third Trimester Pregnant Women - Yuliani, Nur Rohmah; Andarwulan, Setiana (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The study about the efficacy of yoga on second stage progress in third trimester pregnant. Labor is a journey process that will be experienced by pregnant women at the end of pregnancy after entering the age of 36 weeks under normal conditions. Labor will cause feelings of worry for a mother, but childbirth can be passed safely and comfortably without trauma. Prenatal yoga is considered as an alternative to non-conventional efforts to help pregnant women prepare physically, mentally and spiritually for the birth process. This study aims to determine the effect of prenatal yoga on the length of the second stage of labor at Mitra Sehat Mandiri Clinic. The study was conducted with an analytical design with a quasi-experimental primigravida method in the third trimester with a sample of 30 pregnant women who were divided into two groups, namely 15 maternity mothers who attended prenatal yoga and 15 who did not participate in prenatal yoga. Data analysis used independent t statistical test. The average length of the second stage of labor for women who took part in prenatal yoga was 21.66 with a standard deviation of 1.17, while those who did not do yoga were 42.76 with a standard deviation of 2.98. The conclusion is that there is an effect of third trimester yoga exercise on the length of the second stage of labor in mothers with P value = 0.000. Mothers who practice prenatal yoga before delivery will be better prepared to face labor, focus their thoughts and provide inner peace.